2019
DOI: 10.1021/acsnano.8b06515
|View full text |Cite
|
Sign up to set email alerts
|

WS2 Nanotubes, 2D Nanomeshes, and 2D In-Plane Films through One Single Chemical Vapor Deposition Route

Abstract: We demonstrate a versatile, catalyst free chemical vapor deposition process on insulating substrates capable of producing in one single stream one-dimensional (1D) WO3–x suboxides leading to a wide range of substrate-supported 2H-WS2 polymorphs: a tunable class of out-of-plane (of the substrate) nanophases, with 1D nanotubes and a pure WS2, two-dimensional (2D) nanomesh (defined as a network of webbed, micron-size, few-layer 2D sheets) at its extremes; and in-plane (parallel to the substrate) mono- and few-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 90 publications
2
31
0
Order By: Relevance
“…Together with 2D materials, metal surfaces/interfaces of single layer thickness, are among the thinnest possible sources of SHG. However, in metal surfaces, the typical frequency conversion efficiency is of ≈10 −15 .…”
Section: Electromagnetic Hotspots and Hot Electronsmentioning
confidence: 99%
“…Together with 2D materials, metal surfaces/interfaces of single layer thickness, are among the thinnest possible sources of SHG. However, in metal surfaces, the typical frequency conversion efficiency is of ≈10 −15 .…”
Section: Electromagnetic Hotspots and Hot Electronsmentioning
confidence: 99%
“…Generally, WO 3 is always the first choice as a cheap and easily handled precursor with relatively low melting and evaporation temperature [70]. WO 3 can be easily volatized to the sub-oxide WO 3-x [71], rendering the growth of WS 2 by CVD operable in the low pressure and atmospheric pressure systems [72,73]. However, the aforementioned proposed mechanisms were applicable to the growth of WS 2 nanotubes.…”
Section: Gas-phase Synthesismentioning
confidence: 99%
“…However, the aforementioned proposed mechanisms were applicable to the growth of WS 2 nanotubes. Till recently, Liu et al [71] demonstrated the possible mechanism of using WO 3−x as the intermediate to guide the growth of 2D WS 2 . Their results manifested the growth of 2D in-plane WS 2 followed the principle of "self-seeding and feeding", in which short WO 3-x nanorods were acted as both the nucleation sites and the precursor material (Fig.…”
Section: Gas-phase Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Rong’s group [ 28 ] achieved precise control over S introduction time by utilizing a two-zone furnace and obtained very large area WS 2 films of 370 μm domain size. Recently, Liu et al [ 36 ] reported sequential synthesis of several one-, and two-dimensional nanomaterials by intentionally creating initial low sulfur conditions, to divide the growth process in two stages: the first stage is a partial reduction and the second one is sulfurization. By this, they could exploit a WO 3- x intermediate route, and were able to grow large size WS 2 (150 µm).…”
Section: Introductionmentioning
confidence: 99%